2014
DOI: 10.1007/s13762-014-0592-1
|View full text |Cite
|
Sign up to set email alerts
|

Chelator-enhanced phytoextraction of copper and zinc by sunflower, Chinese cabbage, cattails and reeds

Abstract: The phytoextraction of copper and zinc assisted by the chelators such as ethylene diamine tetraacetic acid, diethylene triamino pentaacetic acid, ethylene diamine disuccinate and citric acid into sunflowers (Hh can act as effective cation exchangers. The negatively charged chelator complexes prevented binding to the cell walls of the roots and allowed complexes to enter the cells. Organic content contains fewer soil nutrients and has fewer negatively charged functional groups, such as carboxical, phenolical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Therefore, most of the heavy metals in the soil cannot be directly absorbed by the plants. Chelants have been used as soil extractants to disturb the balance between the solid and liquid phases of contaminates in the soil, increasing the concentration of soluble metals, which is likely to promote the uptake of heavy metals by a high-biomass plant [14,25].…”
Section: Chelant-induced Phytoextractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, most of the heavy metals in the soil cannot be directly absorbed by the plants. Chelants have been used as soil extractants to disturb the balance between the solid and liquid phases of contaminates in the soil, increasing the concentration of soluble metals, which is likely to promote the uptake of heavy metals by a high-biomass plant [14,25].…”
Section: Chelant-induced Phytoextractionmentioning
confidence: 99%
“…We could then remove the metal-rich biomass from the site and store it in an area where it does not pose a risk to the environment. However, results from studies on the stimulating effects of chelants on shoot metal accumulation in different plant species have been largely inconsistent [7,[13][14]. Moreover, the addition of chelants to the soil can directly or indirectly affect plant health, soil microbial properties, and heavy metal concentrations in both soils and plants [15].…”
Section: Introductionmentioning
confidence: 99%
“…In which, the four most frequently used chelates are EDTA, EDDS, DTPA and CA (Yeh et al, 2014). In previous years, EDTA was widely used because of its high efficiency in treating heavy metals in the soil.…”
Section: Integrated Phytoremediation 41 Chelating Agents Enhanced Phmentioning
confidence: 99%
“…The effectiveness of using chelates in support of phytoremediation depends on the choice of plant species and the types of metals stored in the soil (Yeh et al, 2014). Some recent studies have shown and compared the effectiveness of using different chelates to enhance phytoremediation.…”
Section: Integrated Phytoremediation 41 Chelating Agents Enhanced Phmentioning
confidence: 99%
“…Currently, there are many reports about the fertilizer responses of nitrogen, phosphorous and kalium in rice-rape rotation, while there is little research on the heavy metals in rice-rape rotation [12]. However, on the one hand, as plants grow up, heavy metals are accumulated and transported within them [13]. On the other hand, the activity of heavy metals in soils is being changed under the interference of various agricultural activities.…”
mentioning
confidence: 99%